en - Arik Sintya Dewi, Ni Kadek; Udayana, I Nyoman (e-Journal of Linguistics; Vol 14 No 2 (2020): e-jl July, 2020)
This research aims to 1) identify and describe the ability of kindergarten learners in producing English dental fricatives and 2) identify and describe the effect of audio-visual media for kindergarten learners’ ability in producing English dental fricatives. This research used experimental approach with Intact Group Comparison design. The subject of this research was kindergarten learners in Bali Star Academy. The data of this research was collected through documentation method and was analyzed by using qualitative description. The result showed that control group had higher result compared to experiment group during the pre-test with 60.71% average score for the control group and 17.71% average score for the experiment group. After the audio-visual media applied for the experiment group, the result changed into 76.28% average score for the experiment group and 67.85% for the control group.